Inventer son genre dans le langage de la télévision - Catherine Gonnard; Elisabeth Lebovici (Glad!)
Between 1955 and 1969 the French national television has allowed forms of self-presentation and relationnalities, related to non heteronormative cultures and sociabilities. Broadcast regularly, a number of variety shows deployed a range of extraordinary performances. Invisible to an unaware audience, these "pre-Stonewall” figures would never have identified as lesbian, gay or trans. They nevertheless contributed in constituting the francophone post-war lesbian culture as an object of study for queer theory.